PENGEMBANGAN MODEL PEMBELAJARAN AKTIVITAS KEBUGARAN JASMANI MELALUI ALAT SCAR (SPEED, COORDINATION, ACCURACY, REACTION) UNTUK PENDIDIKAN JASMANI (Indonesian Journal for Physical Education and Sport, 2020)
The purpose of this study is to explain and implement the development of learning models of physical fitness activities through the SCAR (Speed Coordination Accuracy Reaction) tool for Physical education This research is the Research and Development (R & D). The following research procedure: 1) the potential and problems, 2) data collection, 3) product design, 4) validation of design (1 expert physical education and 2 learning experts), 5) revised design, 6) test a small scale (30 learners ), 7) revision products, 8) large trial (80 learners), 9) revision products, 10) which produces a tool of mass-production. The results of the initial product expert validation study obtained an average (79%) are very good, with some revisions such as a net adjustment to the size of the ball and shorten the distance of the game. The results of of small scale trials obtained an average of 87% (excellent). The result of the revision of the expert stated that it was very appropriate to use. The results of large-scale trials obtained an average of 93% (excellent). Based on the analysis of research, SCAR tool (Speed, Coordination, Accuracy, Reaction) can be used as a teaching model of physical fitness activities in schools.